Co-occurrence of viral and bacterial pathogens in disease outbreaks affecting newly cultured sparid fish - García-Rosado, Esther; Cano, Irene; Martín-Antonio, Beatriz; Labella Vera, Alejandro Manuel; Manchado, Manuel; Alonso, María del Carmen; Castro, Dolores; Borrego, Juan José (Springer, 2007)
Several microbial disease outbreaks in farm stocks of newly cultured sparid fish species, such as common seabream, redbanded seabream, and white seabream, were recorded from 2004 to 2006. This study describes the isolation and characterization of the potential causative agents, either bacteria or viruses, of these outbreaks. The isolated bacterial strains were characterized according to traditional taxonomical analyses and sequencing of a 16S rDNA fragment. Most bacteria were identified as Vibrio spp. and Photobacterium damselae subsp. damselae. The development of cytopathic effects (CPE) on different fish cell lines, the application of specific nested-PCR tests for infectious pancreatic necrosis virus (IPNV), viral nervous necrosis virus (VNNV) and viral hemorrhagic septicemia virus (VHSV), and subsequent sequence analyses were used for virus detection and identification. VNNV, related to the striped jack neural necrosis virus (SJNNV) genotype, and VHSV, related to the genotype Ia, were the only viruses detected. VNNV was isolated from the three fish species under study in five different outbreaks, whereas VHSV was isolated from common seabream and white seabream during two of these outbreaks. IPNV was not detected in any case.
Keywords: Espáridos - Enfermedades; Espáridos - Virus; Bacterias patógenas; Vibrio spp; Photobacterium damselae subsp. damselae; Virus: VNNV, VHSV; Sparid fish; Co-occurrence of pathogens